1988
DOI: 10.1063/1.341838
|View full text |Cite
|
Sign up to set email alerts
|

Physical model of photostimulated luminescence of x-ray irradiated BaFBr:Eu2+

Abstract: A dynamical model of the temporal dependence of photostimulated luminescence of the storage phosphor BaFBr:Eu2+ as a result of preceeding x-ray irradiation is presented. The model is based on a monomolecular recombination mechanism. The commonly used bimolecular mechanism leads to contradictions with experimental observations. The monomolecular recombination is explained by the existence of a photostimulable luminescence complex with a recombination center and an electron trap in close proximity. Charge transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(62 citation statements)
references
References 10 publications
4
56
0
1
Order By: Relevance
“…The EPR signal of Eu 2+ did not change upon prolonged X-irradiation [34], nor could a change be observed in the Eu 2+ luminescence [47]. Furthermore, the observation of an almost temperature independent PSL effect by stimulating F(Br --) centres from 4.2 K to RT [25] contradicts the model that electrons move through the conduction band upon photostimulation of F centres. Note that a repeated and extended study of the PSL temperature dependence revealed a strong temperature dependence [26].…”
Section: Psl Active Hole Trap Centresmentioning
confidence: 45%
See 3 more Smart Citations
“…The EPR signal of Eu 2+ did not change upon prolonged X-irradiation [34], nor could a change be observed in the Eu 2+ luminescence [47]. Furthermore, the observation of an almost temperature independent PSL effect by stimulating F(Br --) centres from 4.2 K to RT [25] contradicts the model that electrons move through the conduction band upon photostimulation of F centres. Note that a repeated and extended study of the PSL temperature dependence revealed a strong temperature dependence [26].…”
Section: Psl Active Hole Trap Centresmentioning
confidence: 45%
“…It was found that the decay of the photostimulated luminescence under continued stimulation is temperature independent [48] and that the increase in the PSL intensity is proportional to the X-ray dose [25]. This latter result implies that retrapping of electrons after photostimulation does not occur, which makes electron-hole recombination via tunnelling more likely than via the conduction band.…”
Section: Psl Active Hole Trap Centresmentioning
confidence: 62%
See 2 more Smart Citations
“…Eu-doped alkali halides have been introduced to such phosphors. In particular, barium fluorobromide doped with Eu 2+ (BaFBr:Eu 2+ ) has been investigated extensively as a phosphor which is capable to store X-ray information (von Seggern et al, 1988;Koschnick et al, 1991;Thomas et al, 1991). Takahashi et al (1984) and Iwabuchi et al (1994) Kawano and Ueda, 1966).…”
Section: Photostimulated Luminescence and The Imaging Platementioning
confidence: 99%